(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: As one of the most valuable genetic resources of Ongole beef cattle globally, the Sumba Ongole (SO) cattle population is being studied in this investigation of myostatin (MSTN) gene polymorphism and its association with growth traits. Materials and Methods: Blood samples from 161 SO cattle were collected and analyzed. Deoxyribonucleic acid (DNA) was isolated. The DNA was electrophoresed and extracted, and finally, the annealing temperature was optimized, followed by amplification and sequencing. Next, we used a Basic local alignment search tool to assess the sequencing data. Results: The analysis revealed 22 single nucleotide polymorphisms (SNPs) in the MSTN gene in this region that showed genetic variation. Two SNPs, c.424 G > A, and c.467 G > C, were found to be significantly associated with SO cattle phenotypes of wither height, heart girth, and hip height (p < 0.05) but not with body weight or body length (p > 0.05). Conclusion: As a result of our findings, the MSTN gene polymorphism and its correlation with growth traits in SO cattle may be employed as a candidate marker in SO cattle and other beef cattle breeds. J. Adv. Vet. Anim. Res., 9(4): 565–572, December 2022 http://doi.org/10.5455/javar.2022.i625